2015
DOI: 10.1039/c5ra07508d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid functionalised carbon supports for Pd–Ni–Sn catalyst on ethanol oxidation reaction

Abstract: The sodium borohydride reduction method was employed to prepare a ternary catalyst with an atomic ratio of 20%Pd10%Ni10%Sn impregnated on four carbon supports, Vulcan XC-72R carbon black (CB), functionalised carbon black (CB sn ), multi-walled carbon nanotubes (MWCNTs) and functionalised MWCNTs (MWCNT sn ), to improve the catalytic activity for direct ethanol fuel cells (DEFCs). The acid functionalisation was performed using H 2 SO 4 and HNO 3 . The addition of Ni and Sn metals helped to increase catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…2A and B. As expected according to the ECSA values, Pt 55 Pd 38 Bi 7 /C shows the best catalytic activity ($2.30 A mg À1 ) among three Pt x Pd 93Àx Bi 7 /C samples, slightly better than PdNiSn/C (2.15 A mg À1 ), 43 and $2 times better than the commercial Pt/C ($1.20 A mg À1 ). Two well-dened oxidation peaks were clearly observed in Fig.…”
Section: Resultssupporting
confidence: 77%
“…2A and B. As expected according to the ECSA values, Pt 55 Pd 38 Bi 7 /C shows the best catalytic activity ($2.30 A mg À1 ) among three Pt x Pd 93Àx Bi 7 /C samples, slightly better than PdNiSn/C (2.15 A mg À1 ), 43 and $2 times better than the commercial Pt/C ($1.20 A mg À1 ). Two well-dened oxidation peaks were clearly observed in Fig.…”
Section: Resultssupporting
confidence: 77%
“…Moreover, it would modify the Pd geometry and electronic configuration and tune in its adsorption characteristics. Ni has been proven a beneficial cocatalyst when added to Pd because it can generate OH at a lower applied potential and modify the electronic structure of Pd [ 22 , 23 , 24 , 25 , 26 , 27 ]. The coexistence of Ni and Ni(OH) 2 can enhance alcohol oxidation on transition metals in acidic and basic electrolytes [ 6 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [50,62–64] have reported the existence of diffusion restrictions in carbon micropores after other different chemical treatments. Therefore, the reduction of the surface area after H 2 O 2 functionalization could be caused by the blockage of part of the micropores.…”
Section: Resultsmentioning
confidence: 99%
“…As it is observed, the surface area value for CNT and VC supports decreases after functionalization treatment by approximately 24 and 32 %, respectively. Some authors [50,[62][63][64] have reported the existence of diffusion restrictions in carbon micropores after other different chemical treatments. Therefore, the reduction of the surface area after H 2 O 2 functionalization could be caused by the blockage of part of the micropores.…”
Section: Resultsmentioning
confidence: 99%